The Empathize Approach In Visual Communication Design: A Case Study Of The Poznan Company × Real Madrid Community Apparel Campaign - M Akhdan Al Ghifari; Ipung Kurniawan Yunianto (UNIVERSITAS PAKUAN, 2026)
The visual identity of football fan communities constitutes a collective symbol system that, to date, has received limited scholarly attention within the field of visual communication design (VCD), particularly from an empathize-based perspective. This study aims to describe how the empathize stage was operationalized in the VCD process of the Poznan Company × Seputar Real Madrid apparel campaign, to examine how the identity and emotions of Real Madrid fans were translated into visual elements, and to assess audience response indicators as markers of visual resonance—rather than as causal evidence of marketing success. A descriptive-qualitative case study approach was employed, drawing on digital observation of the Seputar Real Madrid community, documentation of campaign visual assets, and engagement and sales conversion data as supporting evidence. Findings reveal that the empathize approach produced three identity-driven visual pillars: the Cibeles Monument and UEFA Champions League (UCL) trophy as iconic symbols, Spanish-language typography anchored by the slogan